The cholesterol-derived metabolite dendrogenin A functionally reprograms breast adenocarcinoma and undifferentiated thyroid cancer cells. Issue 192 (September 2019) - Bauriaud-Mallet, Mathilde; Vija-Racaru, Lavinia; Brillouet, Séverine; Mallinger, Arnaud; de Medina, Philippe; Rives, Arnaud; Payre, Bruno; Poirot, Marc; Courbon, Fréderic; Silvente-Poirot, Sandrine
Graphical abstract: Highlights: DDA induces NIS expression and iodine uptake in MCF7 breast cancer cells. DDA induces a functional differentiation in thyroid cancer cells. The induction of iodine uptake in breast and thyroid cells by DDA is LXR-dependent. Abstract: Dendrogenin A (DDA) is a tumor suppressor mammalian cholesterol-derived metabolite and a new class of ligand of the Liver X receptor (LXR), which displays tumor cell differentiation. In human MCF7 breast adenocarcinoma cells, DDA-induced cell differentiation was associated with an increased accumulation of neutral lipids and proteins found in milk indicating that DDA re-activates some functions of lactating cells. Active iodide transport occurs in the normal lactating mammary cells through the sodium/iodide symporter (NIS) and iodide (I) is secreted into milk to be used by the nursing newborn for thyroid hormones biosynthesis. In the present study, we assessed whether DDA may induce other characteristic of lactating cells such as NIS expression and iodine uptake in MCF7 breast cancer cells and extended this study to the papillary B-CPAP and undifferentiated anaplastic 8505c thyroid cancer cells. Moreover, we evaluated DDA impact on the expression of thyroid specific proteins involved in thyroid hormone biogenesis. We report here that DDA induces NIS expression in MCF7 cells and significantly increases the uptake of 131-I by acting through the LXR. In addition, DDA induces phenotypic, molecular and functional characteristics of redifferentiation in the two human thyroid carcinoma cell lines and the uptake of 131-I in the undifferentiated 8505c cells was associated with a strong expression of all the specific proteins involved in thyroid hormone biosynthesis, TSH receptor, thyroperoxidase and thyroglobulin. 131-I incorporation in the 8505c cells was stimulated by DDA as well as by the synthetic LXR ligand, GW3965. Together these data show that the re-differentiation of breast and thyroid cancer cells by DDA, is associated with the recovery of functional NIS expression and involves an LXR-dependent mechanism. These results open new avenues of research for the diagnosis of thyroid cancers as well as the development of new therapeutic approaches for radioiodine refractory thyroid cancers.